Emotional Support For Early Mobilization On day 0 Until 4 In Patient Post Operation Total Knee Replacement - Agung Widiastuti; Muzaroah Ermawati Ulkhasanah; Amik Muladi; Niya Nurmawati; Muhammad Syaiful Anam (LPPM Universitas Duta Bangsa Surakarta, 2021)
Patients after Total Knee Replacement (TKR) surgery will experience physical mobility and pain obstacles, so that support is needed for these patients. Purpose: This study analyzes whether there is a relationship between emotional support and early mobilization from 0 to 4 days after TKR surgery. Research Methods: Bivariate analysis in this study using Spearman rho total sample of 47 respondents with consecutive sampling method. Results: The study showed that emotional support was associated with mobilization on the first day (p <0.001) and the fourth day (p <0.03). On the first day of mobilization, the patient still feels severe pain, so emotional support or assistance is needed when doing the mobilization. With the assistance, the patient feels confident in doing the exercises. Meanwhile, on the fourth day, the patient has started walking exercises so that emotional support is needed. With the emotional support, the patient feels comfortable and loved, thereby accelerating the healing process. Conclusion: There is a relationship between emotional support for mobilization on the first day and the fourth day post TKR surgery.